Computer techniques for electromagnetics - Mittra, Raj (International series of monographs in electrical engineering, 1973)
Computer Techniques for Electromagnetics discusses the ways in which computer techniques solve practical problems in electromagnetics. It discusses the impact of the emergence of high-speed computers in the study of electromagnetics. This text provides a brief background on the approaches used by mathematical analysts in solving integral equations. It also demonstrates how to use computer techniques in computing current distribution, radar scattering, and waveguide discontinuities, and inverse scattering. This book will be useful for students looking for a comprehensive text on computer techni.